2011
DOI: 10.21121/eab.2011219567
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in The Use of Internet for Health Information Search

Abstract: Demand for health related information is expanding. People seeking health information have many options today. Internet is becoming an important source of information for health related activities in recent years because of its convenience and large capacity. Once consumers enter the domain of electronic health care information, the issue becomes determining the quality of the available information. How do consumers perceive the quality of online health information? This study addresses gender differences in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
(55 reference statements)
3
5
0
1
Order By: Relevance
“…The finding that majority of the respondents (97%) were using the Internet to seek Internet health information was not surprising considering that the Internet provides volumes of health information such as information on preventing and managing chronic diseases, causes or symptoms of common illness, sexual reproductive health, diagnosis and drug information, nutrition, fitness and exercise information, and many others, and since one study revealed that majority of the current generation of young people are known to have difficulties in accessing mainstream health services, the Internet becomes a convenient option for their health care needs. This finding is supported by similar works such as [2,3,14,[18][19][20][21][22][23][24][25]. The current study further noted that causes or symptoms of diseases, management or treatment of conditions, nutrition and exercise, and drug information were the major health information determiners for using the Internet.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The finding that majority of the respondents (97%) were using the Internet to seek Internet health information was not surprising considering that the Internet provides volumes of health information such as information on preventing and managing chronic diseases, causes or symptoms of common illness, sexual reproductive health, diagnosis and drug information, nutrition, fitness and exercise information, and many others, and since one study revealed that majority of the current generation of young people are known to have difficulties in accessing mainstream health services, the Internet becomes a convenient option for their health care needs. This finding is supported by similar works such as [2,3,14,[18][19][20][21][22][23][24][25]. The current study further noted that causes or symptoms of diseases, management or treatment of conditions, nutrition and exercise, and drug information were the major health information determiners for using the Internet.…”
Section: Discussionsupporting
confidence: 89%
“…In addiction, it was unsurprising that an estimated 73% of the students surveyed were using "key word searching" to fulfill their health-related information searching needs plausible due to the fact that this is what they are used to, and also may be, key word searching is a convenient form of conducting their searches. This finding is supported by similar works such as [3,13,24,25]. This study revealed a very important finding, that majority were not using electronic databases to retrieve health information.…”
Section: Discussionsupporting
confidence: 84%
“…Since men and women differ in many aspect eHealth Literacy is also thought to be a term worth checking for the difference. In a study conducted by Yaşin and Özen (2011) in Turkey, women were found to perceive eHealth information quality higher than men. A study held by Bidmon and Terlutter (2015) in Germany found that women had more positive attitude toward web and were more willing to use online sources for searching health-related information.…”
Section: Gender Difference In Ehealth Literacymentioning
confidence: 95%
“…However, a large body of research has documented the significance of gender differences in the adoption behavior of information technologies of varying types, whereas the aspect of gender differences has not been an area of research on the adoption and acceptance of e-technologies in different medical contexts and settings (Wilkowska et al, 2010). In the meantime, a few studies have attempted to examine the effect of gender variations in the adoption of different e-healthcare applications such as: acceptance of a clinical reminder system (Zheng et al, 2006), the use of online health information (Harbour & Chowdhury, 2007), the adoption of medical assistive devices (Wilkowska et al, 2010;Kowalewski, 2012), the use of the web for health information search (Yaşin & Özen, 2011), the acceptance of an invasive medical stent (Ziefle & Schaar, 2011), and the healthcare seeking behavior of tuberculosis patients (Kaur et al, 2013). Apparently, studies on m-healthcare adoption are scare and the findings already documented in literature are fragmented.…”
Section: Gender and Technology Adoptionmentioning
confidence: 99%